Atributos físicos do solo cultivado com plantas de cobertura sob dois regimes hídricos - Ramos, Raquel Cristina (2018)
Among the soil conservation practices used to improve soil quality and production, we highlight the use of plants with a cover function, which are arranged on or embedded in the soil surface, contribute to the maintenance of humidity, reduction of extremes temperature and increase of organic matter, reflecting positively on the physical attributes of soil. The objective was to evaluate the physical attributes of the soil with the use of cover crops under two water regimes for two years in order to contribute to the adoption of no-tillage system in the northern region of Espírito Santo. The work was conducted in the field, in a dystrophic Yellow Argisol, using experimental design in DBC, in subdivided plots, in a 2 x 6 factorial scheme, with four replications. The cover plants evaluated were: four cultivars of Pennisetum glaucum (ADR 300, ADR 500, ADRf 6010 and BRS 1501), Brachiaria ruziziensis and Canavalia ensiformis; the irrigation depths were 76 mm (L1) and 38 mm (L2). (Ds), total pore volume (VTP), microporosity (Mi), macroporosity (Ma), geometric mean diameter (DMG) and weighted mean diameter (DMP); hydraulic conductivity of the saturated soil (Ksat) and soil penetration resistance (RMP). In the first year of cultivation, few significant differences were observed in the attributes Ds, DMG and DMP in the 0-0,2 m layer. In general, higher soil densities were observed in the largest leaf, regardless of the cover species used. Soil density increased in the second year, but there was the effect of the cover plants on the two irrigation slides with the time reducing the PR, indicating improvement in soil quality. Cover plants interfere in the improvement of physical attributes, especially in situations of water stress. ADRf 6010 is the millet cultivation more indicated 11 as a cover plant for 76 mm blade. And B. ruziziensis was the plant with the best results for 38 mm.